Drugs and their ototoxic potentials - Bruneri, Giovanna de Oliveira S.; Borin, Fabiane Yuri Yamacita; Oliveira, Geise Ellen Broto (Revista Terra & Cultura: Cadernos de Ensino e Pesquisa; Vol 38 No especial (2022): Farmácia, 2022)
Hearing is of great importance for communication and socializing. Medicines that have high ototoxic degrees affect hearing by compromising the cochlear and vestibular system, in which case the damage caused may be irreversible. There are several classes of drugs that may have ototoxicity as an adverse effect, and monitoring patients who use ototoxic drugs is difficult. This article aimed to show the main pharmacological classes that have ototoxic potentials and to clarify if there are ways to prevent hearing loss when the use of these drugs is essential for the treatment of illness. The research to be carried out is based on a bibliographic review, where studies of drugs with ototoxic potential were made, which cause hearing-related problems ande need profissional follow-up, through ear exams and serum monitoring of the drugs being administered, bringing challenges to the multiprofissional team.